A dinâmica e a estrutura do conhecimento na inovação aberta: um estudo de caso em uma multinacional de open source - Castro, Ana Elisa Martins Pacheco de (2010)
While companies compete directly in the same industry, this does not mean that innovate in the same way. With this the search for partnerships has been identified as a common practice among companies perceived as effective and internalization of R&D, strategic before, is giving way to new forms open collaborative. Understanding how companies manage the open knowledge for sustainable competitive advantage is the central question of this research. Because it is a subject little explored in Brazil, there is little clarity about the types of knowledge shared within the open collaborative networks. This makes it necessary to broaden knowledge about collaboration and knowledge. To increase this understanding, this research will present a single case study, conducted in a leading company in its industry, which funded its business model on open innovation. The research was made possible by the innovative adaptation of the organization's two conceptual models: a collaboration that helped in the classification of innovative internal staff and listed the characteristics of each one, and another of knowledge, which evaluated the types of knowledge shared between actors open innovation with the aim of seeking to relate the success of the company's innovative model of the nature of knowledge among innovative agents affairs. The results indicated that the dynamics of knowledge happens through the exchange of knowledge hierarchy. Companies that make use of open innovation are inserted at specific times of the spiral of knowledge of the community of practice and implement innovations, and generally incremental, depending on the model established by communities of practice. Note, therefore, the existence of managerial implications for the use of open innovation. It is expected that the results of this study provide knowledge to advance the studies on knowledge management in open innovation